KEPASTIAN HUKUM PEMEGANG SERTIFIKAT HAK MILIK DITINJAU DARI KEBERADAAN LEMBAGA RECHTSVERWERKING (Studi Beberapa Sengketa Hak Milik di Kota Padang) - Azmi Fendri; Yussy A. Mannas (ADHAPER: Jurnal Hukum Acara Perdata, 2020)
Land is a very important entity for human life. There are no activities carried out that are not in contact with land. In its development, land is not only a form of one’s existence, but as an economic value that guarantee one’s life. It is important that land tenure is not only in physical form but also legal control based on rights. In order to realize the community’s desire for land control, an activity known as land registration is carried out. In regulation, land registration is regulated in Government Regulation No. 24 of 1997 concerning Land Registration. In this provision, there is a principle that guarantees legal certainty for certificate holder, namely the rechtsverwerking institution. The existence of this institution was aimed to provide legal certainty to proprietary right holders of land. However, in reality, this principle does not work as desired, because the judiciary continues to base decisions on the facts found in court.